1981
DOI: 10.1038/bjc.1981.194
|View full text |Cite
|
Sign up to set email alerts
|

Application of monoclonal antibodies to purified CEA in clinical radioimmunoassay of human serum

Abstract: Summary.-Double-antibody radioimmunoassay using a mouse monoclonal anti-CEA (MA/1) has been used to measure CEA in human serum. Low levels of MA/1 -binding CEA have been found in serum from normal individuals and moderately raised levels are sometimes associated with certain non-malignant diseases. As with conventional anti-CEA, the MA/i antibodies can recognize significant amounts of CEA in serum from patients with a variety of solid tumours. However they appear to recognize a different immunodeterminant and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1983
1983
1990
1990

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…One of the arguments for changing from an assay using a polyclonal antibody to one with a monoclonal antibody could be the expectation of greater speci- Rogers et al (9) described a monoclonal antibody with a preference for CEA in the serum of stomach carcinoma patients. Staab reported that the present Röche assay was more specific for CEA isomers from patients with colon carcinoma than the Röche radioimmunoassay with polyclonal antiserum (6).…”
Section: Discussionmentioning
confidence: 97%
“…One of the arguments for changing from an assay using a polyclonal antibody to one with a monoclonal antibody could be the expectation of greater speci- Rogers et al (9) described a monoclonal antibody with a preference for CEA in the serum of stomach carcinoma patients. Staab reported that the present Röche assay was more specific for CEA isomers from patients with colon carcinoma than the Röche radioimmunoassay with polyclonal antiserum (6).…”
Section: Discussionmentioning
confidence: 97%
“…Binding of purified CEA antigen, crude CRC cell extract or human plasma was highest with catcher antibodies C.20-32, Bl.l, B6.2, and 5E91E9 using MoAb 5E91E9 or C420-32 as tracer. MoAb C420-32 could trace the antigen bound by catcher MoAb B6.2, indicating that the purified Bl.l 5E91E9 0-3 3.1-6.0 6.1-13 14-25 26-50 51-100 85 22 8 CEA preparation also contained some of the low-molecular-weight CEA-related protein. MoAb B6.2 as catcher followed by MoAb C420-32 as tracer showed high binding activity when incubated with a pooled plasma sample from five healthy donors.…”
Section: Ddia For Antigen Detection In Ssfm and Human Seramentioning
confidence: 93%
“…(22). On the other hand, two other groups (23,24) did not obtain increased clinical specificity or sensitivity with assays using MAbs.…”
Section: Methodsmentioning
confidence: 99%